Transpapillary iridium-192 wire in the treatment of malignant bile duct obstruction. Issue 2 (February 1988) - Levitt, M D; Laurence, B H; Cameron, F; Klemp, P F
Abstract : Twenty four patients with malignant bile duct obstruction were treated with intraluminal radiotherapy using iridium-192 wire inserted through an endoscopically placed nasobiliary catheter. Biliary drainage after treatment was maintained by an endoprosthesis. The median dose of intraluminal radiotherapy was 6000 cGy; two patients with cholangiocarcinoma were given a second course because of disease extension; four patients with pancreatic carcinoma received additional external irradiation (3000 cGy). There was one early death from a cerebrovascular accident (30 day mortality, 4.2%). Cholangitis (30%) was the major early complication and stent blockage (40%) the major late complication; there were no complications directly attributable to radiotherapy. The median survival for patients with pancreatic carcinoma was 250 days and for cholangiocarcinoma, 300 days. This method is technically feasible and may prove safer than the transhepatic technique. The ability of intraluminal irradiation to improve palliation or lengthen survival in patients with malignant bile duct obstruction remains uncertain. Assessment by a prospective, controlled trial is essential.